Impact of the April Fair on Seville hotel room prices: measurement through a hedonic approach - Soler,Ismael P. (2017)
Despite its importance as a tourist attraction, sparse research regarding tourism and hospitality has been focused on Seville's April Fair. That is why the main purpose of this paper is to assess the impact the April Fair and other key elements have on hotels, using the well-known hedonic price model and a database of 1,548 items compiled using TripAdvisor. The results suggest that although the April Fair has a significant and positive effect on the prices of hotel rooms, these results are mixed during the fair. Specifically, the effects of the April Fair can be felt during the weekdays when fairgoers add to those visiting the city on business. However, during the weekend, fair prices do not differ from a non-April day fair. In addition, prices on Sunday Fair are lower than average prices on non-April Fair days. This has important implications for both hotels and organisers of the event. In addition, the results show how the category begins to lose importance in relation to the assessment of the quality perceived by customers. Some implications and solutions are discussed below